Chernozems of Ukraine and its evolution under the influence of anthropogenic factors - Гавриш, Наталія Степанівна; Гавриш, Н.С.; Гавриш, Наталия Степановна; Havrysh, Natalia S.; Позняк, Степан Павлович; Позняк, С. П.; Pozniak, Stepan P.; Ямелинець, Тарас Степанович; Ямелинець, Т. С.; Ямелинец, Тарас Степанович; Yamelynets, Taras S. (University of Agronomic Sciences and Veterinary Medicine of Bucharest, 2021)
Materials of researches on chernozems of Ukraine, features of their genesis, distribution conditions are generalized and analyzed. The general morphogenetic characteristics of chernozems are given, which consists in a typical habitus, constitution, posture, power, unique properties and high fertility. Stability in the development of chernozems is characterized, in particular the stage of their extensive agro-technological use, which determines the intensive development of degradation processes. The role and significance of chernozems in the world of soils as a phenomenon of nature, the ideal of soil, provider and means of labor are emphasized.

Узагальнено та проаналізовано матеріали досліджень чорноземів України, особливості їх генезису, умови поширення. Наведено загальну морфогенетичну характеристику чорноземів, яка полягає в типовому габітусі, конституції, поставі, потужності, унікальних властивостях та високій родючості. Характеризується стабільність у розвитку чорноземів, зокрема стадія їх екстенсивного агротехнологічного використання, що визначає інтенсивний розвиток деградаційних процесів. Підкреслено роль і значення чорноземів у світі ґрунтів як явища природи, ідеалу ґрунту, постачальника та засобів праці.
Pozniak S. Chernozems of Ukraine and its evolution under the influence of anthropogenic factors / S. Pozniak, N. Havrysh, T. Yamelynets // Scientific Papers. Series A. Agronomy. - Vol. 64(2). - University of Agronomic Sciences and Veterinary Medicine of Bucharest, 2021. - P. 156-164.
Keywords: chernozem; fertility; degradation; plowing; soil ideal; natural phenomenon; чорнозем; родючість; деградація; оранка; ідеальний ґрунт; природне явище; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Soil science